Children's Media Use and Homework Time - Sabrina Wulff Pabilonia (Institute for the Study of Labor (IZA), 2015)
Homework is an important part of the academic production function, but often students are studying while doing another activity. Using the nationally representative Panel Study of Income Dynamics-Child Development Supplement time diaries, this chapter explores changes over the period 19972008 in homework time for U.S. children in 1st through 12th grade when homework is done as a sole activity versus simultaneously with another activity. It documents with which technologies and media homework is done simultaneously and how the share of multitasking time differs by gender. This chapter also examines the correlation between childhood attention difficulties and multitasking while studying.
Keywords: J24; 330; multitasking; homework; human capital